Access to oral health care services for children with disabilities: a mixed methods systematic review - Maram Ali Alwadi; AlBandary Hassan AlJameel; Sarah R Baker; Janine Owens (BMC, 2024)
Abstract Background Children with disabilities experience poorer oral health and frequently have complex needs. The accessibility of oral health care services for children with disabilities is crucial for promoting oral health and overall well-being. This study aimed to systematically review the literature to identify the barriers and facilitators to oral health care services for children with disabilities, and to propose priority research areas for the planning and provision of dental services to meet their needs. Methods This was a mixed methods systematic review. Multiple databases searched included MEDLINE, Scopus, PsycINFO, EMBASE, and CINAHL. The search strategy included Medical Subject Heading (MeSH) terms related to children, disabilities, and access to oral health. Eligibility criteria focused on studies about children with disabilities, discussing the accessibility of oral health care. Results Using Levesque's framework for access identified barriers such as professional unwillingness, fear of the dentist, cost of treatment, and inadequate dental facilities. Facilitators of access offered insight into strategies for improving access to oral health care for children with disabilities. Conclusion There is a positive benefit to using Levesque's framework of access or other established frameworks to carry out research on oral healthcare access, or implementations of dental public health interventions in order to identify gaps, enhance awareness and promote better oral health practices. The evidence suggests that including people with disabilities in co-developing service provision improves accessibility, alongside using tailored approaches and interventions which promote understanding of the importance of dental care and increases awareness for professionals, caregivers and children with disabilities. Trial registration Protocol has been registered online on the PROSPERO database with an ID CRD42023433172 on June 9, 2023.